2018
DOI: 10.1016/j.fsi.2018.09.037
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of mycobacterial infection-induced changes to host lipid metabolism in a zebrafish infection model reveals a conserved role for LDLR in infection susceptibility

Abstract: Changes to lipid metabolism are well-characterised consequences of human tuberculosis infection but their functional relevance are not clearly elucidated in these or other host-mycobacterial systems. The zebrafish-Mycobacterium marinum infection model is used extensively to model many aspects of human-M. tuberculosis pathogenesis but has not been widely used to study the role of infection-induced lipid metabolism. We find mammalian mycobacterial infection-induced alterations in host Low Density Lipoprotein met… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…ESAT-6 has been shown to play a role in the infection of M. tuberculosis [ 94 ], as well as in the escape from phagosomes. ESX-1 has also been shown to play a role in inducing the differentiation of macrophages into foam cells [ 100 ], which is necessary for the acquisition of LDLR by the bacterium. While not all members of the genus Mycobacterium possess a ESX-1 secretion system, it has recently been reported that ESX-4 could play a similar role in the regulation of intracellular growth and phagosomal escape [ 101 ].…”
Section: Virulence Factorsmentioning
confidence: 99%
“…ESAT-6 has been shown to play a role in the infection of M. tuberculosis [ 94 ], as well as in the escape from phagosomes. ESX-1 has also been shown to play a role in inducing the differentiation of macrophages into foam cells [ 100 ], which is necessary for the acquisition of LDLR by the bacterium. While not all members of the genus Mycobacterium possess a ESX-1 secretion system, it has recently been reported that ESX-4 could play a similar role in the regulation of intracellular growth and phagosomal escape [ 101 ].…”
Section: Virulence Factorsmentioning
confidence: 99%
“…HSP72 and LDLR were the most targeted genes by the H37Rv-specific miRNAs. These genes are involved in the interaction between neutrophils and macrophages during the early phase of the innate immune response to Mtb infection (52) as well as in the control of infectious load and infection-induced changes in lipid metabolism (53), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Infections were studied through the natural route using bath exposures and it was observed that the gastrointestinal track was the primary route of infection [102]. The M. marinum infection-induced lipid metabolism was furthermore studied using the zebrafish model [112,113].…”
Section: Bacteriamentioning
confidence: 99%